2015
DOI: 10.1371/journal.pone.0117332
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review Concerning the Relation between the Sympathetic Nervous System and Heart Failure with Preserved Left Ventricular Ejection Fraction

Abstract: BackgroundHeart failure with preserved left ventricular ejection fraction (HFPEF) affects about half of all patients diagnosed with heart failure. The pathophysiological aspect of this complex disease state has been extensively explored, yet it is still not fully understood. Since the sympathetic nervous system is related to the development of systolic HF, we hypothesized that an increased sympathetic nerve activation (SNA) is also related to the development of HFPEF. This review summarizes the available liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 73 publications
1
46
0
2
Order By: Relevance
“…Our present findings may be the result of the activation of the sympathetic nervous system. The riser BP pattern is caused by autonomic nervous system dysfunction, and activation of the sympathetic nervous system has been observed in HFpEF . Therefore, sympathetic nervous system activation in HFpEF is one of the causes of the riser BP pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Our present findings may be the result of the activation of the sympathetic nervous system. The riser BP pattern is caused by autonomic nervous system dysfunction, and activation of the sympathetic nervous system has been observed in HFpEF . Therefore, sympathetic nervous system activation in HFpEF is one of the causes of the riser BP pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Sympathetic overdrive has been documented in these patients as well. Verloop and colleagues recently concluded that the current availability of knowledge does not permit a distinguishment on whether enhanced sympathetic activity results in HFpEF, or HFpEF results in enhanced sympathetic activity (Verloop et al, 2015). Moreover, whether patients with HFmrEF present with a hyperadrenergic state, and the eventual magnitude of this alteration, remains to be documented clinically.…”
Section: Hyperadrenergic State In Heart Failurementioning
confidence: 99%
“…However, substantial efforts are needed to identify changes in neural-cardiovascular regulatory pathways in HFpEF patients. Indeed, these patients also have prominent autonomic dysfunction (Verloop et al, 2015). However, little is known about the role of neural mechanisms that govern the amplitude or frequency of bursts of autonomic activity, or the pattern of active fiber discharge.…”
Section: Introductionmentioning
confidence: 99%
“…4) Therapeutic targeting to block excessive sympathetic activation in HF could reduce morbidity and mortality. 5) While numerous types of inhibition of sympathetic activity are being investigated, renal sympathetic denervation (RDN) is an interventional treatment option for patients.…”
mentioning
confidence: 99%